Quality by Design: Optimization of Letrozole Solid Lipid Nanoparticle for Breast Cancer - Priyadarsini, Sowmya; Lahoti, Swaroop Rameshwarji (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: Hormone responsive breast cancer is the most prevalent cancer worldwide. Letrozole is a third-generation aromatase inhibitor widely used for the treatment of advanced breast cancer. The primary objective of the present work is to develop and optimize an injectable solid lipid nanoparticle incorporating letrozole to circumvent the side-effects of a marketed conventional formulation and thereby improve patient compliance. Materials and Methods: Emulsification solvent evaporation and melt dispersion techniques were used for formulating the said solid lipid nanoparticles. Quality by design concept was used for the development and optimization of formulation and process variables. Results: The optimum level selected is 60 mg lipid, 30 mg surfactant, and co-surfactant, 15000 psi HPH pressure, and 15 HPH passes. Conclusion: Glyceryl dibehenate was selected as suitable lipid based on solubility and partition coefficient. With an increase in lipid content there is increase in particle size and PDI and decrease in entrapment efficiency. Higher surfactant and co-surfactant concentrations result in lower particle size, PDI, higher zeta potential, and lower entrapment efficiency. An increase in HPH pressure reduced particle size and PDI up to a certain level, however, the increase in HPH pressure from 15000 to 20000 psi increased particle size. An increase in the number of HPH passes reduces particle size and PDI. The drug release mechanism for LTR-SLN was found to follow the first order and higuichi model.
Keywords: Solid lipid nanoparticle; Letrozole; Ishikawa diagram; Plackett burman design; Central composite design; Mathematical modeling